"Homosexual men whose lives turned out unsuccessful": Polish aunties in the transition era. Issue 3 (3rd July 2022) - Janion, Ludmiła
ABSTRACT: This article investigates how the term ciota (aunty) was employed in mainstream media in the 1990s to exclude some gay men from visibility politics, and also how it was appropriated to counter these exclusions. The social, economic, and political changes of the 1990s disadvantaged "aunties" who were accused of hindering emancipation. I argue that ciota became what Judith Butler refers to as the "constitutive outside" to the masculine, restrained, and monogamous gay man. However, when given voice in the media, aunties presented gay femininity and cruising as a historic or even noble tradition, thus troubling the dominant condemnatory narrative.